Pattern of Dyslipidemia in Diabetes Mellitus in Tertiary Hospital of Nepal - Gajurel , R M; Pant, P (Journal of Institute of Medicine Nepal, 2014)
Introduction: Dyslipidemia is a preventable major risk factor for coronary heart disease (CHD). Despite an increased risk of CHD in diabetes, little is known concerning awareness and adequacy of dyslipidemia treatment in this population. Patients with type I Diabetes Mellitus are at an increased risk for coronary heart disease. Hence, the study aimed to evaluate the pattern of dyslipidemia in patients with Diabetes Mellitus in tertiary care hospital. Methods: This is a prospective, cross-sectional, descriptive study of Diabetes Mellitus admitted in Medical units of TUTH. History was taken by preformed questionnaires and patients were clinically examined. A series of baseline investigations including fasting, lipid profile was done. Patients were followed up till discharge. Results: A total 120 diagnosed diabetes mellitus patient were enrolled in the study. Total serum cholesterol level was high in 33.3%, serum triglyceride was elevated in 18.3%, LDL cholesterol was raised in 21.7% and HDL cholesterol was low in 20%. Majority of the study patients 69.2% were found to be in poor status of Glycemic control with HbA1c level more than 7 % and 30.8% were in good control with HbA1c level less than 7%. Among poor Glycemic control group, 84.4% had HbA1c level between 7-12% and 15.6% had HbA1c level >12%. Conclusion: Dyslipidemia, a major risk factor for CHD, remains largely undiagnosed and undertreated in high risk populations, especially in patients with Diabetes. Increased triglycerides and decreased HDL are the commonest pattern observed in diabetics. Treatment of dyslipidemia with various modalities early in the course of disease helps to prevent macrovascular complications.